Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.jamda.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

End-Stage Renal Disease in Nursing Homes: A Systematic Review

Abstract: Objectives/Introduction Demand for nursing home (NH) care by patients with endstage renal disease (ESRD) is likely to increase with growing numbers of older adults initiating chronic dialysis. We completed a systematic review to summarize the literature on NH residents with ESRD. Methods MEDLINE, CINAHL, EMBASE, and relevant conference proceedings were searched to identify articles using the following MESH terms or related key words in the title or abstract: “residential facilities”, “renal dialysis”, “renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Importantly, we found that a higher number of nondiseasespecific problems was associated with higher risk for death, transition to LTC, and functional impairment. Additionally, previous studies have described the lack of data available on patients with ESRD in nursing homes, and studies that have been conducted have focused on those receiving LTC or among those discharged from SNF care (5,23). We studied the effect of nondisease-specific problems among older adults who were not institutionalized before dialysis initiation, of whom nearly one third were living alone before developing ESRD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, we found that a higher number of nondiseasespecific problems was associated with higher risk for death, transition to LTC, and functional impairment. Additionally, previous studies have described the lack of data available on patients with ESRD in nursing homes, and studies that have been conducted have focused on those receiving LTC or among those discharged from SNF care (5,23). We studied the effect of nondisease-specific problems among older adults who were not institutionalized before dialysis initiation, of whom nearly one third were living alone before developing ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of older adults initiating dialysis do so during a hospitalization, and these patients may require post-acute care services in a skilled nursing facility (SNF) (1,2). Although previous studies of older patients receiving dialysis have reported highintensity hospital care at the time of dialysis initiation and poor health outcomes after dialysis initiation among nursing home residents (2)(3)(4), descriptions of community-dwelling older adults who begin dialysis during a hospitalization and receive subsequent SNF care are limited (5). Because older patients initiating dialysis are medically complex and dialysis can interfere with rehabilitation, they may experience worsening health and may not return home or achieve functional independence (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, older adults comprise nearly one‐third of prevalent US dialysis patients, and this proportion will increase as the population ages. Although a small proportion of older dialysis patients reside in nursing homes, those who live independently in the community have a greater risk of nursing home placement compared to older adults without kidney failure because of a substantially faster rate of functional decline over time . Functional decline is a geriatric syndrome that is characterized as the process of loss of physical and/or cognitive function and manifest as needing assistance with basic activities (eg, walking, dressing, or remembering to take medication) .…”
Section: Introductionmentioning
confidence: 99%
“…The relevant literature suggests that patients with ESRD living in nursing homes have increased morbidity and mortality compared with patients with ESRD who do not. 17 The US Renal Data System reported that the unadjusted overall survival is 26.0% among nursing home residents with ESRD, 41.0% for those with chronic kidney disease (CKD), and 58.0% for non-CKD residents in nursing homes. 8 In our survey, a large percentage of participants considered the LTC setting itself a contraindication to transplantation.…”
Section: Discussionmentioning
confidence: 99%